2012
DOI: 10.1093/ejcts/ezs412
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of risk factors for transient neurological dysfunction and adverse outcome after repair of acute type A aortic dissection in 122 consecutive patients

Abstract: Regardless of standardized neuroprotective techniques, treatment of ATAAD remains a high-risk operation. Preoperatively, the presence of a reduced ejection fraction, a malperfusion syndrome or a high body mass index may increase the perioperative risk for an adverse outcome. A dissection 'entry' localized in the aortic arch or the descending aorta may increase the risk for postoperative stroke. Intraoperatively, cannulation of the femoral artery and extension of the LBI time over 45 min should be avoided. Espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 10 publications
2
48
2
Order By: Relevance
“…Therefore, a low postoperative TND rate (9.5%) with no case of PND observed in our series was not unexpected. Previous studies have identified predictors of the negative neurologic outcomes in surgically treated AADA patients as age, history of cerebrovascular adverse events, renal insufficiency, prolonged hypothermic circulatory arrest time (>40 minutes), and CPB time [2,4,12,15,18,19]. However, in the current study, these risk factors were not found to be independent predictors for postoperative neurologic dysfunction.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Therefore, a low postoperative TND rate (9.5%) with no case of PND observed in our series was not unexpected. Previous studies have identified predictors of the negative neurologic outcomes in surgically treated AADA patients as age, history of cerebrovascular adverse events, renal insufficiency, prolonged hypothermic circulatory arrest time (>40 minutes), and CPB time [2,4,12,15,18,19]. However, in the current study, these risk factors were not found to be independent predictors for postoperative neurologic dysfunction.…”
Section: Discussioncontrasting
confidence: 79%
“…According to the published literature, the overall incidence of TND in AADA patients undergoing hypothermic circulatory arrest and selective cerebral perfusion varies between 2.5-16% and PND with a reported incidence of 4-24% [2,12,15-17,19]. The risk of postoperative neurologic dysfunction was reported to be significantly influenced by the site of arterial cannulation and could be greatly reduced by cannulating a graft sewn to the right axillary artery [5,7,15]. All patients in this study were cannulated through an 8-10 mm Gore-Tex graft sewn to the axillary artery and then received ACP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After evaluating the full-text articles, 14 were finally selected for the systematic review and meta-analysis. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] An overview of the studies and study quality assessment are summarized in Tables 1 and 2, respectively. An outline of the systematic review process is depicted in Figure 1.…”
Section: Selected Studiesmentioning
confidence: 99%
“…The CC group included right axillary artery cannulation in 7 studies, [20][21][22][23][24][25][26] direct aortic cannulation in 2 studies, 18,19 both right axillary artery or direct aortic cannulation in 3 studies, [15][16][17] and right axillary artery or innominate artery or direct aortic cannulation in 2 studies. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] A total of 8 of 14 studies reported on type A aortic dissection cases only, [16][17][18][20][21][22][23]25 whereas the others included mixed aortic pathologies. 14,15,19,24,26,27 Cerebral protection strategies included hypothermic circulatory arrest (HCA), antegrade selective cerebral perfusion (ASCP), and retrograde cerebral perfusion.…”
Section: Selected Studiesmentioning
confidence: 99%